Adaptation and Validation of the Academic Stress Scale in the Italian Context: Latent Structure, Reliability, and Concurrent Validity - Lucrezia Perrella; Ernesto Lodi; Patrizia Patrizi (MDPI AG, 2024)
The present study describes the Italian adaptation of the Academic Stressors Scale (E-CEA) of the Academic Stress Questionnaire, evaluating the relationships with general and domain-specific well-being and verifying the significant predictors and the amount of variance explained by the "non-intellective" academic competencies on the scores of student stress dimensions. The participants are 1305 students from all the different degree courses. The Italian version of the E-CEA, composed of 38 items, showed good psychometric properties both in terms of reliability and factorial structure with good fit indices. The 6 sub-dimensions, for the most part overlapping with those of the original version of the instrument, show good construct and concurrent validity as negative relationships were found with general and domain-specific well-being indices. With regard to the regressions performed, several dimensions of "non-intellective" academic competencies turned out to be significant predictors (with negative effect) with respect to the stress levels perceived in the academic environment by university students: in particular, time organization, emotional control, the ability to relate to professors and intrinsic motivation could decrease stress levels, while dedication to study and the tendency to involve one's parents in one's university career seemed to increase stress levels. Regarding the practical implications of the results, suggestions are provided in supporting the career paths of students to reduce risk factors for stress development and to promote academic well-being.